Electrical and magnetic properties of FM/MgO/FM (FM = Co90Fe10, Fe20Ni80) heterostructures - Aviles Felix, Luis Steven (2016)
In this paper we present the development and characterization of FM/MgO/FM (FM = Co90Fe10, Fe20Ni80) heterostructures. The magnetic order of the structures, magnetic anisotropy and interlayer exchange coupling were characterized by magnetization measurements. The influence of the substrate temperature during growth on the magnetic properties and topographical features of the bottom electrode was also explored. Higher values of the coercive field were achieved increasing the substrate temperature during deposition of the bottom electrode. Patterned magnetic tunnel junctions were grown on Si(1 0 0) and MgO(1 0 0). The junctions consist of square pillars with different areas (1600, 625, 100 and 25 μm2) fabricated by optical lithography. I(V) curves obtained with conducting atomic force microscopy of the patterned junctions were performed at room temperature in order to explore the reproducibility of the transport properties of the insulating barrier. The results show a more insulating behavior of the junctions grown on Si(1 0 0), with very good control and a high reproducibility of the transport properties of the MgO insulating barrier.